ADVANCEMENTS IN IMAGE PROCESSING: EXPLORING EMERGING TECHNOLOGIES AND RESEARCH OPPORTUNITIES - Dubey, Srishti; Yadav, Pragati; Pandey, Shweta; Pandey, Er. Neeraj Kumar (International Journal of Engineering Technologies and Management Research, 2025)
The area of image processing is essential to computer applications in a variety of fields, including physics, computer-aided design, measurement, and 3D simulation. The capabilities of digital image technology have been greatly increased by image processing techniques and improvements in computer hardware. With a focus on its two primary uses—improving visual information for human interpretation and processing image data for autonomous machine perception—this article examines the state of digital image processing technology today. It highlights the uses of image processing in cutting-edge research fields, defines the field's breadth, and describes the main techniques involved.